-(5y+1)-(-4y-7)=2

Simple and best practice solution for -(5y+1)-(-4y-7)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5y+1)-(-4y-7)=2 equation:


Simplifying
-1(5y + 1) + -1(-4y + -7) = 2

Reorder the terms:
-1(1 + 5y) + -1(-4y + -7) = 2
(1 * -1 + 5y * -1) + -1(-4y + -7) = 2
(-1 + -5y) + -1(-4y + -7) = 2

Reorder the terms:
-1 + -5y + -1(-7 + -4y) = 2
-1 + -5y + (-7 * -1 + -4y * -1) = 2
-1 + -5y + (7 + 4y) = 2

Reorder the terms:
-1 + 7 + -5y + 4y = 2

Combine like terms: -1 + 7 = 6
6 + -5y + 4y = 2

Combine like terms: -5y + 4y = -1y
6 + -1y = 2

Solving
6 + -1y = 2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1y = 2 + -6

Combine like terms: 6 + -6 = 0
0 + -1y = 2 + -6
-1y = 2 + -6

Combine like terms: 2 + -6 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| 2w=5 | | 102-6x=21x+15 | | 15m^2-10m-25= | | 5x+5=-150-10x | | y=ty | | 12=-3s | | 50m^3-2m= | | 2w-w=4 | | 3m^2-10m+8= | | 10n^2-3n-1= | | x^2-18x=72 | | 2w-w=5 | | 1-9n^4= | | s+34=14 | | 2w+1-w=5 | | 2n^2+11n+15= | | 2n^2+11a+15= | | 2.13x=10 | | 5n^2+9n-2= | | n^2+4n-21= | | n^2+4a-21= | | 4+(x+0)= | | 12.5+4.5(x-3)=62 | | 2(x+8)=8(x+2) | | (3w+1)(w)=14 | | 2x-13=99 | | 3w+1(w)=14 | | 21=3n^3-3 | | 12x^2-60+75=0 | | 3x^2-18x-3=0 | | 6(8-x)=32-(8-x) | | 5x^2-36x+75=0 |

Equations solver categories